Epigenetics-Based Therapeutics for Neurodegenerative Disorders - Xu, Zihui (2012)
Epigenetic regulation, such as DNA methylation and histone modification, is implicated in the aberrant changes in gene expression that occur during the progression of neurodegeneration. Many epigenetics-based drugs have been developed recently for the treatment of some neurodegenerative disorders, including Alzheimer’s, Parkinson’s, and Huntington’s diseases. Here we review recent studies that highlight the role of epigenetic modifications in neurodegeneration, among them DNA methylation and demethylation and histone acetylation and deacetylation; we also explore the possibility of using epigenetics-based therapeutics to treat neurodegenerative disorders.